2000
DOI: 10.1161/01.cir.102.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Imaging–Guided Noninvasive Ultrasound Thrombolysis

Abstract: External high-intensity focused ultrasound thrombolysis using optimal PW parameters for periods of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 28 publications
2
79
0
3
Order By: Relevance
“…This increase was reduced when the fibrin gels were degassed, and thus these authors attributed the increase to cavitational activity. Other authors have shown that high intensity focused US produced echo-dense material in the clot, most probably by creating cavitation bubbles [134].…”
Section: Thrombolytic Enzymesmentioning
confidence: 99%
“…This increase was reduced when the fibrin gels were degassed, and thus these authors attributed the increase to cavitational activity. Other authors have shown that high intensity focused US produced echo-dense material in the clot, most probably by creating cavitation bubbles [134].…”
Section: Thrombolytic Enzymesmentioning
confidence: 99%
“…Этот эффект в первую очередь связан с эффектом нестацио-нарной кавитации, т.е. быстрым увеличением и коллап-сом микропузырьков [76,77].…”
Section: сонотромболизисunclassified
“…Thus the effects of clot disruption are obtained more mechanically, and cavitation effects are considered to make the biggest contribution during the process. 3,5,[10][11][12] As a result, high acoustic peak negative pressure (as high as 19 MPa 13 ) at relatively low ultrasound frequencies such as 500 kHz or 1 MHz are used so that cavitation can be effectively induced. However, at such low ultrasound frequencies, the focal spot of the ultrasound field can be larger than 10 mm in length, which is larger than the diameters of most veins.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of intravenously injected microbubbles can enhance the effects of ultrasound and reduce the required energy for producing ultrasound-mediated thrombolysis by decreasing cavitation threshold. 3,12,14,15 Also, a few of studies 16 have shown that HIFU can improve thrombolysis while applying thrombolytic agents by reducing the dosage of the drug and reducing the risk of hemorrhagic events, but increasing its efficacy. In addition, microbubbles and thrombolytic drugs can be combined together for targeted drug delivery, drug transport acceleration [17][18][19][20][21] and eventually enhancing thrombolysis.…”
Section: Introductionmentioning
confidence: 99%